Effects of Components of PM2.5 Collected in Japan on the Respiratory and Immune Systems. (March 2017) - Honda, Akiko; Fukushima, Wataru; Oishi, Mizuki; Tsuji, Kenshi; Sawahara, Takahiro; Hayashi, Tomohiro; Kudo, Hitomi; Kashima, Yuji; Takahashi, Katsuyuki; Sasaki, Hideki; Ueda, Kayo; Takano, Hirohisa
Epidemiologic studies have reported that particulate matter with aerodynamic diameters ≤2.5 μm (PM2.5 ) affect respiratory diseases, including asthma. The components and/or factors of PM2.5 that contribute to the exacerbation of asthma have not been identified. We investigated the effects of extracts of PM2.5 collected in Japan on the respiratory and immune systems. PM2.5 was collected from an industrial area and an urban area in December 2013. Airway epithelial cells and immune cells were exposed to aqueous or organic extracts of PM2.5 . Exposure to extracts from both areas, especially to organic extracts rather than aqueous extracts, caused a pro-inflammatory response via interleukin (IL) 6 production from airway epithelial cells, and it induced the maturation/activation of bone marrow–derived antigen-presenting cells via dendritic and epithelial cell (DEC) 205 and cluster of differentiation (CD) 86 expression and proportional changes in the constitution of the splenocytes. The extracts collected from the industrial area tended to show greater effects than those from the urban area. These results suggest that organic components of PM2.5 affect the respiratory and immune systems. These effects can differ by the collection areas. In addition, IL-6, DEC205, and CD86 can be predictive biomarkers for the respiratory and immune effects of ambient PM2.5 .